DNA Computing towards the Solution of Minimum Vertex Cover Problem - J. , Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
DNA computing is an unconventional method for parallel computation. It is a technique proposed for finding a solution to intractable computational problems. A computational hard problem in which the time complexity can increase exponentially with problem size. This work develops a new DNA-exploring model to solve a minimum vertex cover problem (MVCP). This DNA processing model solves the MVCP in polynomial time calculation.